The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antibiotics11101365
|View full text |Cite
|
Sign up to set email alerts
|

Fidaxomicin for the Treatment of Clostridioides difficile Infection in Adult Patients: An Update on Results from Randomized Controlled Trials

Abstract: In recently updated international guidelines, fidaxomicin is preferentially recommended as first-line treatment over vancomycin both for the first episode of CDI and for rCDI, based on the results of different randomized controlled trials (RCTs). Although noninferiority was the rule in phase-3 RCTs with regard to the primary endpoint of clinical cure, for shaping these recommendations, particular attention was devoted to the improved global cure and reduced risk of recurrent CDI (rCDI) observed with fidaxomici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 101 publications
3
5
0
Order By: Relevance
“…Another study [ 14 ] with a higher percentage of patients treated in the first episode replicated the results of the pivotal trials. Nevertheless, all these post-authorization studies [ 12 , 14 , 26 , 27 ] confirmed the outcomes in both clinical cure and recurrence rate that appeared in the RCT [ 9 , 10 ] varying from 82% to 92% cure [ 12 , 14 , 26 , 27 ], with recurrence rate from 15% to 28% [ 12 , 14 , 16 , 26 , 28 ], similar to our results (cure 84% and recurrence 33% in fidaxomicin group). In addition, Gentry et al reported higher failure rates in patients with severe CDI treated with fidaxomicin compared to vancomycin (9.39% vs. 1.41%), as well as higher combined outcome clinical failure or recurrence at 12 weeks (32% in fidaxomicin vs 25% in vancomycin) [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another study [ 14 ] with a higher percentage of patients treated in the first episode replicated the results of the pivotal trials. Nevertheless, all these post-authorization studies [ 12 , 14 , 26 , 27 ] confirmed the outcomes in both clinical cure and recurrence rate that appeared in the RCT [ 9 , 10 ] varying from 82% to 92% cure [ 12 , 14 , 26 , 27 ], with recurrence rate from 15% to 28% [ 12 , 14 , 16 , 26 , 28 ], similar to our results (cure 84% and recurrence 33% in fidaxomicin group). In addition, Gentry et al reported higher failure rates in patients with severe CDI treated with fidaxomicin compared to vancomycin (9.39% vs. 1.41%), as well as higher combined outcome clinical failure or recurrence at 12 weeks (32% in fidaxomicin vs 25% in vancomycin) [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the IDSA/SHEA guideline updates, a significant consideration is introduced regarding the recommendation of fidaxomicin over a standard course of vancomycin for initial CDI treatment – specifically, the choice of fidaxomicin hinges on resource availability [ 7 ]. The considerable cost associated with fidaxomicin has indeed posed a barrier to its widespread adoption [ 5 , 11 ]. Consequently, the IDSA/SHEA guidelines deem vancomycin as an acceptable alternative to fidaxomicin for patients with an initial CDI [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the FDA advises caution in administering bezlotoxumab, emphasising that it should be considered only when the benefits outweigh the risks in patients with a history of congestive heart failure [ 7 ]. Additionally, there remains limited knowledge regarding the efficacy of fidaxomicin in combination with bezlotoxumab for preventing recurrent CDI [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the benefit has been demonstrated to be higher in most fragile patients [46,47]. Risk group stratification strategies are needed to identify patients who are most likely to benefit from fidaxomicin [48].…”
Section: Discussionmentioning
confidence: 99%